Seeking protection from precarity? Relationships between transport needs and insecurity in housing and employment. Issue 109 (February 2020) - Mullen, Caroline; Marsden, Greg; Philips, Ian
Highlights: Transport planning assumptions about housing, employment and transport are outdated. Precarity in housing and employment systems often mean people have to move. Uncertainty about when move influences decisions on accessibility and transport. Implications for sustainable mobility, urban development and social welfare. Abstract: The importance of the nexus between transport, housing location and employment location has long been identified as important to social welfare. In transport research this has however operated largely at either end of the spectrum of advantage. There exists a strong tradition, with roots in welfare economics, which explores those with choices and how they make trade-offs between where to live and work, the associated wage rate and the commute costs. At the other end is work which recognises the social costs for those that do not have access to transport and struggle to participate in employment. This paper focuses its attention on households that fall between these extremes and for whom the choice/no-choice dichotomy does not work. Through in-depth interviews with 46 people in the UK we find that the interactions between the location and, critically, security of both housing and employment plays a critical role in shaping what 'choices' exist. In particular, the findings explain why some households own cars although, on other metrics, they would not be expected to find ownership affordable, and how the security of housing tenure shapes long-term household trajectories. The literature on planning and travel behaviour has paid little or no attention to the security of housing and employment. This study suggests the importance of addressing this gap and refocussing attention on the different ways in which transport connects to wider planning and social policy.